2019
DOI: 10.1016/j.bone.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone mineral density with hemoglobin and change in hemoglobin among older men and women: The Cardiovascular Health Study

Abstract: Purpose: Osteoblasts and their precursors support hematopoiesis in the bone marrow. We hypothesized that declines in Hgb levels are associated with bone mineral density (BMD). Methods: The Cardiovascular Health Study is a prospective longitudinal study that enrolled 5,888 community-dwelling adults aged >65 years and measured hemoglobin twice, in 1989–90 and 1992–93, as well as BMD by dual-energy X-ray absorptiometry (DXA) in 1994–95. In a subset of 1,513 men and women with a Hgb in 1992–93 and BMD, we used l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
4
24
2
Order By: Relevance
“…Our study also showed significant linear associations between Cre and TG levels and between Cre and AIs and an inverse correlation between Cre and HDL-C levels. A previous study found partial positive associations between Hb level and BMD in men but negative associations in women [33], whereas another study showed no relationship [34]. Interestingly, our data showed a significant positive association of Hb level with lipid profile, except HDL-C level, which showed a significant negative relationship, and AIs.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study also showed significant linear associations between Cre and TG levels and between Cre and AIs and an inverse correlation between Cre and HDL-C levels. A previous study found partial positive associations between Hb level and BMD in men but negative associations in women [33], whereas another study showed no relationship [34]. Interestingly, our data showed a significant positive association of Hb level with lipid profile, except HDL-C level, which showed a significant negative relationship, and AIs.…”
Section: Discussioncontrasting
confidence: 56%
“…[ 24 ] However, a prospective longitudinal study based on cardiovascular health concluded that there was no correlation between the decrease of HGB level and BMD, and neither a single HGB measurement nor longitudinal change in HGB would be useful as a marker of low BMD in the short-term. [ 25 ] Therefore, the clinical utility of these studies remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study showed that high platelet counts are associated with osteoporosis and osteopenia [ 11 ]. Others showed no consistent association between platelet count and bone mineral density (BMD) [ 12 , 13 ]. A few studies have reported a negative association between low hemoglobin (hgb) or anemia and bone density [ 14 , 15 ], or a high annual loss of BMD [ 12 ], although not supported by others [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Others showed no consistent association between platelet count and bone mineral density (BMD) [ 12 , 13 ]. A few studies have reported a negative association between low hemoglobin (hgb) or anemia and bone density [ 14 , 15 ], or a high annual loss of BMD [ 12 ], although not supported by others [ 13 ]. Studies on the association between white blood cells and its subtypes and BMD have shown conflicting results [ 12 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%